COMPARISON OF FOSINOPRIL AND ATENOLOL EFFECT ON HEART 0.1 HZ-RHYTHMS SYNCHRONIZATION AND BLOOD MICROCIRCULATION IN PATIENTS WITH ARTERIAL HYPERTENSION - A. R. Kiselev; V. I. Gridnev; A. S. Karavaev; O. M. Posnenkova; V. I. Ponomarenko; M. D. Prochorov; B. P. Bezruchko (Столичная издательская компания, 2016)
Aim. To compare the effect of fosinopril and atenolol on synchronization of heart 0.1 Hz-rhythms and blood microcirculatory.Material and methods. 63 patients at the age of 47±8 with hypertension (HT) of grade 1-2 were enrolled in the study. 0.1 Hz-oscillations in heart rate variability (HRV) and in filling of microcirculatory bed were registered during passive tilt test under spontaneous breathing. The duration of each stage of test was 10 min. Synchronization was estimated as a phase difference between 0.1 Hz-rhythms of heart rate and filling of microcirculatory bed. Frequency values of HRV spectrum in LF- and HF-ranges were also assessed.Results. Fosinopril and atenolol showed comparable effect on blood pressure (BP) reduction. Atenolol decreased in heart rate significantly. Treatment with either fosinopril or atenolol in patients with significant vegetative dysfunction resulted in repair of functional interaction between heart 0.1 Hz-regulation and microcirculatory bed. Functional dissociation of 0.1 Hz-regulation mechanisms was observed under the treatment with fosinopril or atenolol in patients with initially sufficient interaction.Conclusions. Fosinopril and atenolol influenced similarly on heart 0.1 Hz-mechanisms and microcirculation autonomic regulation in patients with HT. Atenolol is a drug of choice in patients with sympathicotony. Both drugs should be administered in according with an individual level of 0.1-Hz rhythms synchronization assessed before start of the treatment.